Pemanfaatan Batu Sungai Lariang Kabupaten Sigi Pada Campuran AC-WC - Rafael Patiung (Paulus Civil Engineering Journal, 2026)
Around the Lariang River, South Kulawi District, Sigi Regency, there are many materials in the form of river stones that are only used by the community as house foundations, but it does not rule out the possibility that they can be used as asphalt mixture materials for highways. This study aims to determine the aggregate characteristics of the Budong-budong River and assess its feasibility in the AC-WC mixture based on the 2018 Bina Marga specifications. The research method involves laboratory testing of the characteristics of aggregates, asphalt, and fillers, as well as conventional Marshall and Marshall Immersion tests to assess the stability and durability of the mixture. The results showed that the Lariang River aggregate has characteristics that meet the 2018 Bina Marga standards, obtained a Stability value of 1571.17 kg, a flow value of 3.18 mm, a VIM value of 4.01%, a VMA value of 18.76%, a VFB value of 78.61% with Marshall Remaining (SMS) stability reaching 94.13% at an optimum asphalt content of 6.5%.